Peter Pottemager i Slagelse: Kakler og matricer fra pottemagerens affaldsdynge - Kristiansen, Ole (Hikuin, 2001)
Peter Potter in Slagelse. Stove tiles and matrixes from the potter’s waster By Ole Kristiansen In the years 1981-82, the National Museum excavated waster from a Renaissance pottery and stove tile workshop in Slagelse. The potter’s kiln itself was not found, but rejected stove tiles, pipkins, frying pans, bowls and platters, as well as inserts for the kiln, potter’s tools and lead for making glazes indicate activity in the last half of the 16th century and for a couple of decades into the 17th century. More than 60 different types of stove tiles were found – partly as rejects from firing, partly as used, sooty pieces from repairs. Based on the history of clothing and German aristocracy, and on graphical depictions and varying glazes, they can be dated from 1531 at the earliest to shortly after 1611, with the main part from around 1600. The 12 more or less fragmented matrixes are all older, namely from the middle of the 16th century. One matrix has on its reverse the mark of an unidentified maker. A stove tile pattern differing slightly in eastern and western Zealand shows an individual finishing touch given to matrixes moulded in the same patrix and indicates two centres of stove tile production. However, matrixes seem to be imported exclusively from Germany; only for one item can a Danish artist be assumed. It is shown that graphical works by Aldegrever (1531), Flötner (1546), Maarten de Vos (1581), and a student of Goltzius (1589) were directly used and that Dürer and Cornelis Bos provided strong inspiration. Stove tiles found in nearby villages are remarkably identical with the older matrixes and the younger tiles from the Slagelse workshop. Based on the investigation of traces from production and use found on matrixes and tiles, with subsequent attempts at reconstruction, the patrix, matrix and stove tile production and the shape of the tiled stove are discussed.